Pengaruh Media Virtual Labs Berbasis Problem Based Learning (PBL) Terhadap Hasil Belajar Peserta Didik Kelas XI MIA SMA Negeri 1 Jeneponto (Studi pada Materi Pokok Titrasi Asam Basa) - Suarni, Suarni; Husain, Halimah; Salempa, Pince (Jurnal Riset Pendidikan Kimia (JRPK), 2022)
This study is a quasi-experimental research which aims to determine the effect of using virtual labs media in problem based learning (PBL) model toward students learning outcomes in class XI MIA SMA Negeri 1 Jeneponto study on acid base titration. This study design used is posttest-only control group design. These study population were all the students of class XI MIA of SMAN 1 Jeneponto which consists of six classes. The sampling technique is simple random sampling. The class XI MIA 3 as experiment group and XI MIA 5 as control group each of which consists of 31 students, the learning process is carried out online. Technique of collecting data of the learning result done by giving post-test to experiment group dan control group. In analysing the data, the researcher used descriptive and inferential statistics. The result of the analysis shows that the average of learning outcomes of experiment group is 77,47 higher than the control group is 62,25. Result of hypothesis test by using Mann-Whitney test with α = 0,05 (non-parametrik test) obtained that H1 is accepted and H0 is rejected. It shows that there is an influence of using virtual labs media in problem based learning (PBL) model toward students learning outcomes in class XI MIA SMA Negeri 1 Jeneponto study on acid base titration. Keywords: Virtual labs, problem based learning, learning outcomes.